Proses Informasi pada Peringatan Kesehatan dalam Kemasan Rokok - Pamungkas, Yoma Bagus (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2017)
Â Consumption of tobacco use is very high, no exception in Indonesia. Therefore, the government through the Ministry of Health decreed the regulation of health warning in the each cigarette package. The regulation includes the Pictorial Health Warning (PHW) and Health Information Message (HIM) which aims to reduce interest smoke. The purpose of this article is to examine more deeply about how an information process that occurs in health warnings on cigarette packaging can be conveyed to the smokers to reduce smoking. In explaining the process, The Author uses the concept of Attention and Message Processing, Elaborative Processing, Cognitive Response Theory, Fear Appeals and Fear Arousal. The result shows that on health warnings indicate that there is coherence between external stimuli (fear appeal) which described by Elaboration Likelihood Model (ELM) with cognitive meaning by smokers, so that can evoke fear in their self to quite smoking. Â Keywords : Pictorial Health Warning Label (PHW), Health Information Message (HIM), Attention and Message Processing, Elaborative Processing, Cognitive Respon Theory, Fear Appeals dan Â Fear Arousal